2001
DOI: 10.1016/s0896-6273(01)00274-4
|View full text |Cite
|
Sign up to set email alerts
|

Extrasynaptic Release of Dopamine in a Retinal Neuron

Abstract: Extrasynaptic release of dopamine is well documented, but its relation to the physiological activity of the neuron is unclear. Here we show that in absence of presynaptic active zones, solitary cell bodies of retinal dopaminergic neurons release by exocytosis packets of approximately 40,000 molecules of dopamine at irregular intervals and low frequency. The release is triggered by the action potentials that the neurons generate in a rhythmic fashion upon removal of all synaptic influences and therefore depends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
51
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(57 citation statements)
references
References 54 publications
(3 reference statements)
6
51
0
Order By: Relevance
“…We (Fig. 2D) and others (7,10) have found that L-type Ca 2ϩ channels, which are known to be loosely associated with release machinery (34,35), mediate somatic exocytosis. In contrast, N-and P/Q types Ca 2ϩ channels, which are closely associated with fusion machinery, are involved in the exocytosis at synaptic terminals (34,36).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…We (Fig. 2D) and others (7,10) have found that L-type Ca 2ϩ channels, which are known to be loosely associated with release machinery (34,35), mediate somatic exocytosis. In contrast, N-and P/Q types Ca 2ϩ channels, which are closely associated with fusion machinery, are involved in the exocytosis at synaptic terminals (34,36).…”
Section: Discussionsupporting
confidence: 52%
“…It has been assumed for a long time that the cell body (i.e., soma) of a neuron does not release transmitters in response to electrical stimulation. This assumption has been challenged by our and others' observations that neuronal somatic release indeed occurs (3)(4)(5)(6)(7)(8)(9)(10). Using carbon fibers, several groups have shown that somatic release of catecholamine occurs through vesicular mechanisms (3,(5)(6)(7).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…granules (34). The distribution of organelles containing the vesicular monoamine transporter-2 suggests that dopamine-containing vesicles are of the agranular type.…”
Section: Discussionmentioning
confidence: 99%